2008
DOI: 10.1007/s10620-008-0365-0
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Celiac Disease in Blood Donors in Iceland

Abstract: Prevalence of celiac disease in Iceland is similar to what has been reported in many other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…All nine children with doctor-diagnosed CD had undergone blood testing for CD but only 44% had an intestinal biopsy performed. The prevalence of CD in our study was similar to that in other industrialised countries,35 as well as a previous study in the adult New Zealand population 9. The only prior publication on CD prevalence among New Zealand children,10 which was conducted more than two decades ago, showed a significantly lower prevalence of CD (0.014%) compared to our study, a difference that suggests significant under-ascertainment in the earlier study or significant increases in the incidence and general awareness of CD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…All nine children with doctor-diagnosed CD had undergone blood testing for CD but only 44% had an intestinal biopsy performed. The prevalence of CD in our study was similar to that in other industrialised countries,35 as well as a previous study in the adult New Zealand population 9. The only prior publication on CD prevalence among New Zealand children,10 which was conducted more than two decades ago, showed a significantly lower prevalence of CD (0.014%) compared to our study, a difference that suggests significant under-ascertainment in the earlier study or significant increases in the incidence and general awareness of CD.…”
Section: Discussionsupporting
confidence: 89%
“…In summary, we found that the prevalence of doctor-diagnosed CD in New Zealand children is similar to that in adult New Zealanders and the population prevalence in other industrialised countries 35 9. We also found that gluten avoidance was five times more common than the prevalence of doctor-diagnosed CD.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…11 These data and previous reports of high prevalence of CD in the “Fertile Crescent” challenges the hypothesis of a Middle East-Europe CD prevalence gradient attributable to a lack of exposure to cereals until relatively recently (Simoons’ hypothesis).…”
Section: Introductionmentioning
confidence: 82%
“…There were 15 studies on blood donors, which fulfilled our inclusion criteria. [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] The prevalence of CD in blood donors based on EMA was 0.21-1.34%, 0.14-7.01% based on elevated tTG levels, while 0-0.62% had Marsh 3 lesions. Twenty-nine studies on first-degree relatives fulfilled our inclusion criteria.…”
Section: Incidence and Prevalence Of Clinically Diagnosed CD (Tables mentioning
confidence: 99%